Epidemiological analysis of mental health morbidity in Tamil Nadu - Damodharan Dinakaran; Arpitha Krishna; Aravind Raj Elangovan; Senthil Amudhan; Selvi Muthuswamy; Chellamuthu Ramasubramanian; Palanimuthu T. Sivakumar; Girish N. Rao; Gopalkrishna Gururaj; Mathew Varghese; Vivek Benegal (Indian Journal of Psychiatry)
Background: Existing psychiatric epidemiological studies from Tamil Nadu with methodological limitations and variations had under-reported the prevalence of mental morbidity. Robust data from a representative population-based epidemiological study are not readily available to guide mental health programs in Tamil Nadu. Aim: This study aimed to estimate the prevalence, correlates, and treatment gap of mental morbidity in the state of Tamil Nadu using data from National Mental Health Survey (NMHS) of India, 2015–2016. Materials and Methods: NMHS in Tamil Nadu was conducted in 60 clusters of 4 districts (Trichy, Tirunelveli, Thoothukudi, and Namakkal) using a door-to-door survey and multistage sampling proportionate to rural, urban nonmetro, and urban metro population. Mini-International Neuropsychiatric Interview (M.I.N.I version 6) and Fagerstrom nicotine dependence scale were administered on a representative adult (aged ≥18 years) sample to assess the mental morbidity. Prevalence and 95% confidence intervals (CIs) were estimated after weighing the sample for survey design. Results: A total of 3059 adults from 1069 households were interviewed. The overall weighted prevalence of lifetime and current mental morbidity was 19.3% (95% CI: 19.0%–19.6%) and 11.8% (95% CI: 11.6%–12.0%) respectively. Participants who were men (largely contributed by substance-use disorders), aged 40–49 years, from rural areas, and from lower income quintile had higher prevalence of mental morbidity. The treatment gap was 94.2% for any mental health problem. Common mental disorders (depression, anxiety, and substance-use) accounted for most of the morbidity. Conclusion: The burden and treatment gap for mental health morbidity is high in Tamil Nadu. The findings call for urgent policy level and systemic action to strengthen mental health program in Tamil Nadu.